The Adsorptive Acid Orange 7 using Kenya tea Pulps Ash from Aqueous Environments - Hamed Biglari (Journal of Global Pharma Technology, 2017)
The control of environmental pollutions specially water resource pollutions is one of the main challenges throughout the world. The discharge of industrial wastewater such as textile industries containing toxic dyes like acid orange 7 has added to this concern. In this research, the adsorption of acid orange 7 anionic dye on the raw fine-grained tea waste modified with an acid and calcined has been investigated through the adsorption method. To achieve this purpose, the adsorbents of fine-grained CTC tea waste were studied in three forms of raw, treated with concentrated phosphoric acid, and calcined at 350, 450, and 500 °C for the adsorption of acid orange 7 with 50-500 mg/L concentrations from the aqueous conditions at pH 2-10 and t 0-120 min using 1-10 g/L adsorbents. The results showed that the best removal yield is about 98% at pH 2 and time 120 using 50 mg/L of dye and 10 g/L of adsorbent, and the modifications have a negligible effect on the improvement of the raw fine-grained tea waste adsorption. The most adsorption capacity (41.66 mg of orange 7 dye) was obtained using 1 g of the adsorbent. Also, the results illustrated that the adsorption pattern is in agreement with the Langmuir and Freundlich isotherm models. The adsorption pattern in the Freundlich model (R2 97%) is slightly more than Langmuir model (R2 85%). According to the granulated structure of tea waste (fine-grained tea) in three forms of raw, acidic and calcined, Kenya is an appropriate and low-cost adsorbent in the adsorption of orange 7 dye from the aqueous media.Keywords: Water pollution, Adsorption, Kenya tea waste, Acid orange 7dye